From dopamine to muscarine: xanomeline-trospium (KarXT) as a novel direction in the psychopharmacotherapy of schizophrenia - Żełabowski, Kacper; Pichowicz, Wojciech; Dembowska, Julia; Szwajkowski, Maciej; Mykhailova, Daria; Wurm, Grzegorz; Biedka, Kamil; Błaszczyk, Katarzyna; Piotrowski, Patryk (Frontiers in Pharmacology, 2026)
Schizophrenia is a severe chronic mental disease with considerable prevalence and social load. Its treatment relies on both typical and atypical antipsychotics, whose primary mechanism of action involves dopamine D2 receptor blockade, with atypical agents additionally modulating serotonergic pathways, which partially improves tolerability but does not adequately address cognitive symptoms. Xanomeline–trospium (KarXT) is the first FDA-approved drug for schizophrenia treatment via cholinergic receptor modulation. The antipsychotic feature of xanomeline lies in its M1 and M4 muscarinic receptor agonism in the central nervous system. Trospium does not cross the blood–brain barrier and acts as a peripheral muscarinic antagonist, thereby reducing the side effects of xanomeline, which also exerts peripheral activity. In Phase II and III clinical trials conducted between 2016 and 2023 (EMERGENT-1 to EMERGENT-5), KarXT demonstrated statistically significant reductions in psychotic symptoms, measured by the Positive and Negative Syndrome Scale compared with placebo in short-term randomized studies, with moderate effect sizes, and sustained symptom improvement and stable tolerability over 52 weeks in long-term extension trials. They also reported a favorable tolerability profile, with frequent mild gastrointestinal side effects. An important finding is that KarXT does not affect dopaminergic transmission and therefore does not cause the expected side effects typically associated with D2 receptor blockers, including extrapyramidal reactions and hyperprolactinemia. This review presents the pharmacological rationale behind KarXT and the current clinical evidence for its efficacy, safety, and proposes a breakthrough in the schizophrenia therapy.